Pengaruh Reward dan Motivasi terhadap Kinerja Karyawan UMKM : Studi pada UMKM Nasi Kulit Syuurga Yogyakarta - Rendi Pranoto; Niken Widyastuti; Bambang Irjanto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Employee performance is a crucial aspect that plays a crucial role in maintaining the sustainability, productivity, and competitiveness of a company, including in the micro, small, and medium enterprises (MSMEs) sector. Optimal performance levels not only impact the achievement of company targets but also influence customer satisfaction and business churn. One factor believed to be able to improve employee performance is the provision of rewards and motivation. Rewards can be financial or non-financial, which serve as a form of company appreciation for employee contributions. Meanwhile, motivation functions as an internal driver that raises work enthusiasm to achieve the best results. This study aims to analyze the effect of rewards and motivation on employee performance at the Nasi Kulit Syuurga MSME. The study used a quantitative descriptive approach with a saturated sampling technique, where the entire population of 32 employees were used as respondents. The research instrument was a structured questionnaire, and the data obtained were analyzed using multiple linear regression methods using SPSS version 25 software. The results showed that rewards have a significant influence on employee performance. This indicates that appropriate recognition can improve work quality and productivity. However, motivation partially did not have a significant effect on employee performance, which is likely caused by other factors such as working conditions, organizational culture, or suboptimal job satisfaction. Nevertheless, rewards and motivation have been shown to simultaneously contribute to improved employee performance. This finding underscores the importance of designing an effective reward system, coupled with more targeted motivation strategies, to enable MSMEs to retain high-performing employees and increase their competitiveness.